Measurement of the B0s → μμ effective lifetime with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; et al. (Journal of high energy physics, 2023)
This paper reports the first ATLAS measurement of the B0s → μμ effective lifetime. The measurement is based on the data collected in 2015–2016, amounting to 26.3 fb−1 of 13 TeV LHC proton-proton collisions. The proper decay-time distribution of 58 ± 13 background-subtracted signal candidates is fit with simulated signal templates parameterised as a function of the B0s effective lifetime, with statistical uncertainties extracted through a Neyman construction. The resulting effective measurement of the B0s → μμ lifetime is 0.99+0.42 −0.07 (stat.) ± 0.17 (syst.) ps and it is found to be consistent with the Standard Model.